Findings of Main Obstacles Facing Thai SMEs Towards Business Growth Sustainability - Tonvongval, Sumontha; Tantivong, Chamaiporn (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
This paper aims to provide insight information into main competencies thirty-four local Small and Medium-sized Enterprises (SMEs) are lacking in order to achieve their business performance and sustained healthy economic growth. The data was obtained from Researchers' five day-planned productivity improvement to individual firms during the year 2017 to 2019 in Nakornpathom, Ratchaburi, Rayong, Samutprakan, and Samutsakorn provinces, and Bangkok. The information reveals that eighteen (18) or 52.94% of both small and medium enterprises have low entrepreneurial skills (the inability to identify and define a viable market niche, recognizing, envisaging, and formulating strategies for taking advantage of opportunities). This study also summarizes the lack of main management skills or competencies of the SMEs based on the study of Mitchelmore & Rowley (2009). The impact of these skills led to Thai SMEs' inability to: smoothly and continuously produce and deliver quality products to customers, keep costs down and compete, and attract and retain talent. Further studies should delve into specific entrepreneurial skills of SMEs owner/managers, which significantly impact firm performance and sustained growth. Consequently, current Thailand's SME promotion policies could be reviewed in order to differentiate existing promotional programs based on the quality of SMEs for their sustained development and effective utilization of SME's budgets.